Au@Pt nanodendrites enhanced multimodal enzyme-linked immunosorbent assay. Issue 18 (1st March 2019) - Jiao, Lei; Zhang, Lianhua; Du, Wenwen; Li, He; Yang, Dingyu; Zhu, Chengzhou
Abstract : Single modal enzyme-linked immunosorbent assay (ELISA) covering colorimetric, fluorescence, and chemiluminescence techniques has been widely reported in recent years, whereas the combination of multiple signal channels in one immunosensing platform still faces huge challenges. Abstract : Single modal enzyme-linked immunosorbent assay (ELISA) covering colorimetric, fluorescence, and chemiluminescence techniques has been widely reported in recent years, whereas the combination of multiple signal channels in one immunosensing platform still faces huge challenges. Multimodal imaging will provide more comprehensive and precise diagnostic information by the combination of two or more imaging modalities. Inspired by this concept, we established a new kind of multimodal enzyme-linked immunosorbent assay (M-ELISA) based on the unique properties of Au@Pt nanodendrites. As a proof-of-concept demonstration, cardiac troponin I (cTnI) has been chosen as a model biomarker. Owing to the excellent photothermal effect and intrinsic peroxidase-like activity of Au@Pt nanodendrites, the concentration of cTnI can be quantificationally reflected by photothermal immunoassay, colorimetric immunoassay and ratiometric fluorescence immunoassay simultaneously. This developed M-ELISA demonstrated the good consistency with the chemiluminescence immunoassay method in clinical diagnosis for real serum samples.